Atención psiquiátrica y psicológica al paciente oncológico en las etapas finales de la vida - Rodríguez Vega, Beatriz; Ortiz, Aranzazu; Palao, Ángela (Psicooncología, 2004)
The goal of this article is to review the most frequent referrals to a psychiatry service of terminally ill cancer patients in a general hospital; the treatment and asociated risk factors will also be reviewed. This treatment will have to be focused on the control of symptoms and on mantaining a good enough quality of life. The psychotherapeutic strategies for the patients and their family caregivers are also exposed; the support to the medical team who is daily facing the failure of their praxis and their own death, is not forgotten. Finally, it is also important to talk about grief after the death of the terminally ill.